Experimental and Numerical Analysis in Carbon Fiber Composite Leaf Spring - Arun Prabhu; K. Arunprasath; S. Jayaprakash; R. Madhubalakrishnan (Journal of Advanced Mechanical Sciences, 2022)
Now-a-days automobile manufacturers around the world is concentrating on weight reduction in the vehicles. Around 10-20% of the mass of the automobile was reduced by reducing the mass of the spring leaf. The carbon fiber leaf spring is fabricated and analyzed for reducing the weight. It was found that the new carbon fiber spring has good load carrying capacity. In addition, it has excellent stiffness. Moreover, it stores high strain energy. It has great strength to mass ratio. The solid model of carbon fiber leaf spring was made through CREO and analysis was executed through Ansys software.